Caracterização nutricional e de compostos bioativos do Xique-Xique (Pilosocereus gounellei (A. Weber ex. K. Schum.) Bly. ex Rowl.) - Bezerril, Fabrícia França (2017)
Cactaceae are abundantly present in the semi-arid region of Northeast Brazil. Among its species, the Xique-xique (Pilosocereus gounellei) is found in the drier regions of the Caatinga biome, which although little knowledge about its constitution, has its use in popular medicine, in the treatment of inflammations, as well as in periods of scarcity is used for food and feed in this region. In this study, water, pH, acidity, soluble solids, moisture, proteins, lipids, sugars, fiber, ash, mineral and amino acid profile, antioxidant activity, phenolic compounds profile and bioaccessibility . The assays were compensated in three experimental groups, called vascular cylinder, central thallus and vascular cylinder + central thallium, highlighting the vascular cylinder region to obtain additional information about the antinutritional factors, phenolic profile and bioaccessibility of these compounds. In the obtained results, differences (p <0.05) were observed between the groups in most of the analyzed variables, except for water, pH and amino acids. In the experimental groups representative amounts of calcium, magnesium, manganese, selenium and zinc were observed, as well as soluble fiber content in the vascular cylinder, as well as the presence of phenolic compounds, such as quercetin and epigallocatechin gallate. In this way, with the study, the xique-xique is visualized as a potential food alternative, pointing out possibilities in the use and enrichment of various food products, with good technological and nutritional quality.